ASSESSMENT OF UNDERGROUND WATER QUALITY AND POLLUTION SOURCES APPORTIONMENT IN A GROWING URBAN CENTRE IN OSUN STATE SOUTH WESTERN NIGERIA. - Timothy O. OGUNBODE; Emmanuel A. AKINTUNDE; Omowumi T. AKINOLA (European Journal of Geography)
Cases of water-associated diseases and deaths have been reported globally especially in developing countries. Thus, a research was conducted to assess the quality of underground sources in a growing urban centre, in Osun State, Nigeria. A sample of well water, that each one was collected from each of the 15 political wards across the five quarters in the town. Physico-chemical parameters were determined and analyzed using standard laboratory techniques. Factor analysis was used to determine the dominant water quality parameters. The results revealed that Nitrate, Phosphate, Sodium, potassium, Calcium, Sulphate, pH, Total Alkalinity, Total Suspended Solids, Total Hardness and Total Dissolved Solids are generally within the maximum permissible limits. Temperature, Electrical Conductivity, and coliform counts were generally above the acceptable limits. The results showed that underground water sources are susceptible to contaminations. It is recommended that proper treatment of the water should be carried out before consumption to safeguard human health.